2021
DOI: 10.1007/s00068-021-01673-5
|View full text |Cite
|
Sign up to set email alerts
|

More than 20° posterior tilt of the femoral head in undisplaced femoral neck fractures results in a four times higher risk of treatment failure

Abstract: Purpose In this study, we aimed to determine the correlation between the preoperative posterior tilt of the femoral head and treatment failure in patients with a Garden type I and II femoral neck fracture (FNF) treated with the dynamic locking blade plate (DLBP). Methods Preoperative posterior tilt was measured in a prospective documented cohort of 193 patients with a Garden type I and II FNF treated with the DLBP. The correlation between preoperative post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Consequently, no threshold for correction has been defined regarding basicervical FNFs. In FNFs, a posterior tilt exceeding the threshold of 20° in Garden type I and II fractures increases the failure rate of osteosyntheses fourfold [ 27 ]. Kalsbeek et al report a rate of treatment failure for FNF Garden type I and II with posterior tilt over 20° being similar to displaced FNFs (Garden type III/IV) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, no threshold for correction has been defined regarding basicervical FNFs. In FNFs, a posterior tilt exceeding the threshold of 20° in Garden type I and II fractures increases the failure rate of osteosyntheses fourfold [ 27 ]. Kalsbeek et al report a rate of treatment failure for FNF Garden type I and II with posterior tilt over 20° being similar to displaced FNFs (Garden type III/IV) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 All studies involved cases using only internal fixation with either 2 or 3 screws, except for one study which also included cases involving a sliding hip screw 9 and one that used a dynamic locking blade plate. 11 Twelve studies divided cohorts into those with preoperative PTA above or below 20 degrees. The remaining 5 either used a different PTA cutoff 15,19,22 or reported a raw value for PTA alone.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…6 It is important to note that there can be fractures classified as "incomplete" or "nondisplaced" Garden I or II with a PTA greater than 20-degrees because the classification is based on an AP radiograph while the angle measurement is based on a lateral radiograph. 2,[9][10][11] The purpose of this systematic review and meta-analysis was to assess the association between preoperative PTA and risk of treatment failure after internal fixation of nondisplaced femoral neck fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that a femoral neck posterior tilt greater than or equal to 20 degrees and an anterior tilt greater than 10 degrees were associated with 1.7–4.7 times higher risk of fixation failure. [ 1 , 2 , 8 , 9 ] By contrast, 2 other studies found no association between sagittal tilt on the lateral view and postoperative complications. [ 7 , 10 ] One possible explanation for the discrepant findings is that the described methods for assessing sagittal deformity may have limited reliability, particularly when dichotomizing fractures as “low-risk” and “high-risk.” Posterior tilt on the lateral radiograph is influenced by rotation and flexion of the femur.…”
Section: Introductionmentioning
confidence: 96%